ДОСЛІДЖЕННЯ МОЖЛИВОСТІ ПЕРЕДАЧІ СИГНАЛУ ЦИФРОВОГО ТЕЛЕБАЧЕННЯ СТАНДАРТУ DVB-T2 ПО РАДІОРЕЛЕЙНІЙ ЛІНІЇ МЕТОДОМ КОМБІНОВАНОЇ МОДУЛЯЦІЇ - Авдєєнко, Гліб Леоніддович; Адамович, Олег Михайлович (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2016)
The research of digital television signal of the DVB-T2 standard transmission possibility via the radio relay line with combined modulation method usage Practical substantiation of development of a new approach with the key feature of the analog radio relay lines with frequency modulation modem equipment adaptation to transmit TV signal of DVB-T2 standard on basis of the principle of double modulation COFDM/ FM is presented.